Embracing the Social Nature of Recovery: A Qualitative Study on the Resource Group Method for People With Severe Mental Illness - Tjaden, Cathelijn D.; Boumans, Jenny; Mulder, Cornelis L.; Kroon, Hans (Frontiers in Psychiatry, 2020)
Objective: The resource group method for people with severe mental illness might provide a useful framework to facilitate patient’s empowerment and systematically engage significant others. However, no research has explored the perspectives and experiences of patients and their significant others. This is crucial for better adjustment to the needs of the people using the method. The aim of this study was to develop a useful framework for a deeper understanding of the resource group method and its outcomes. Method. The study used a longitudinal, qualitative multiple case-study design based on grounded theory methodology. During a period of two years, the developments and processes in eight resource groups were explored by conducting a total of 74 interviews (e.g. with patients, significant others and mental health professionals) and 26 observations of resource group meetings. Results. Analysis showed that a well-functioning resource group set the stage for five processes to unfold: (i) experience of support; (ii) acknowledgment of significant others; (iii) activation; (iv) openness; and (v) integration. These processes facilitated recovery both in terms of an arousing curiosity within the patient as well as increasing reciprocity and equality in their social relations. In addition, the method emphasized the uniqueness of each recovery journey, thereby providing a framework to shape recovery-oriented care. The analysis also revealed three hindering factors: (i) embedding and implementation issues; (ii) predominant network; and (iii) tensions inherent in the resource group setting. Conclusion. Working according to the resource group method involves that the person’s recovery work becomes a social process that takes place in relation to the social environment and everyday life in which it is important to acknowledge and integrate the needs of significant others in treatment and care. This study provides a first step toward a multidimensional comprehension of the resource group method, the working mechanisms and its influence on recovery for people with severe mental illness.